Geographic Constraints on Knowledge Spillovers: Political Borders vs. Spatial Proximity - Singh, Jasjit; Marx, Matt (Management Science, 2013)
Geographic localization of knowledge spillovers is a central tenet in multiple streams of research. However, prior work has typically examined this phenomenon considering only one geographic unit—country, state, or metropolitan area—at a time and has rarely accounted for spatial distance. We disentangle these multiple effects by using a regression framework employing choice-based sampling to estimate the likelihood of citation between random patents. We find both country and state borders to have independent effects on knowledge diffusion beyond what just geographic proximity in the form of metropolitan collocation or shorter within-region distances can explain. An identification methodology comparing inventor-added and examiner-added citation patterns points to an even stronger role of political borders. The puzzling state border effect remains robust on average across analyses, though it is found to have waned with time. The country effect has, in contrast, not only remained robust but even strengthened over time. This paper was accepted by Kamalini Ramdas, entrepreneurship and innovation.